Pediatric diseases: textbook - Кильдиярова, Р. Р. педиатрия Рита Рафгатовна (Textbook, 2022)
The textbook refl ects the current level of knowledge on the most common childhood diseases. The edition clearly and easy-to-follow sets out all sections of pediatrics: history of pediatrics, propedeutics of childhood diseases, neonatology and pathology of early childhood, allergology and pulmonology, cardiology and rheumatology, gastroenterology and hepatology, nephrology, hematology and immunology, endocrinology, children infectious diseases, as well as emergency pediatrics. The textbook is written in accordance with the program of the Pediatrics discipline, it is distinguished by systematization, clarity, the possibility of independent study of the material and further self-control. Intended for students studying in educational institutions of higher and secondary medical education, as well as students of additional professional education.